2017
DOI: 10.4269/ajtmh.17-0271
|View full text |Cite
|
Sign up to set email alerts
|

Undiagnosed Active Pulmonary Tuberculosis among Pilgrims during the 2015 Hajj Mass Gathering: A Prospective Cross-sectional Study

Abstract: Mass gatherings pose a risk for tuberculosis (TB) transmission and reactivation of latent TB infection. The annual Hajj pilgrimage attracts 2 million pilgrims many from high TB-endemic countries. We evaluated the burden of undiagnosed active pulmonary TB in pilgrims attending the 2015 Hajj mass gathering. We conducted a prospective cross-sectional study in Mecca, Kingdom of Saudi Arabia, for nonhospitalized adult pilgrims from five high TB-endemic countries. Enrollment criteria were the presence of a cough and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 24 publications
2
39
2
Order By: Relevance
“…Most TB cases in the current study were males and over half were above 50 years old with primary or no formal education. This is in accordance with global and Hajj-related data and established risk factors for TB [1,7,10,12]. However, the prevalence of coexisting chronic diseases (63%, 17/27) among TB patients, especially diabetes, was higher than that reported internationally as well as previous studies among Hajj pilgrims with TB [7,[12][13][14].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Most TB cases in the current study were males and over half were above 50 years old with primary or no formal education. This is in accordance with global and Hajj-related data and established risk factors for TB [1,7,10,12]. However, the prevalence of coexisting chronic diseases (63%, 17/27) among TB patients, especially diabetes, was higher than that reported internationally as well as previous studies among Hajj pilgrims with TB [7,[12][13][14].…”
Section: Discussionsupporting
confidence: 90%
“…Around 28% (8/29) of the TB cases reported being current smokers and a similar proportion (5/18) indicated that they did smoke in the past. This is higher than that reported in another study among Hajj pilgrims with TB (13.3%) [7] but lower than figures from some international reports [15,16]. Other risk factors for TB such as visit to, or residence in high-burden countries and occupational exposure were uncommon among TB patients in the study and so was previous Hajj or Umrah performance.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…37 A large percentage of Hajj pilgrims come from high tuberculosisendemic coun tries. The burden of undiagnosed active pulmonary tuberculosis in pilgrims attending the 2015 Hajj from five high tuberculosisendemic countries was evaluated by a study randomly screening 1164 pilgrims, 36 of which 15 had previously undiagnosed active pulmonary tuberculosis. With millions of pilgrims visiting Saudi Arabia from high tuberculosis endemic areas, cases of undiagnosed active pulmonary tuberculosis will continue to pose a risk to other pilgrims.…”
Section: Infectious Diseases At the Hajjmentioning
confidence: 99%